Reducing Loneliness in Undergraduate Students through E-Journaling Intervention: A Pre-Experimental Study - Rahmadianty Gazadinda; Gayatri Wisya Putri; Herdiyan Maulana (Bulletin of Counseling and Psychotherapy, 2023)
The Covid-19 pandemic in Indonesia has had a devastating psychological impact on society, with the rise of online interaction failing to replace face-to-face interaction, particularly among undergraduate students. Loneliness is a prevalent mental health problem among students during the pandemic. This study aimed to assess the effectiveness of e-journaling intervention in reducing loneliness among undergraduate students. A pre-experimental design was used, with 38 undergraduate students participating in writing activities in the form of journaling every weekday for two weeks. Pre and post-tests were given using the De Jong Giervield Loneliness Scale to evaluate loneliness. The results of a Wilcoxon signed-rank test showed no significant difference in loneliness before and after the intervention, with only 40% of participants showing a decrease in loneliness. This suggests that e-journaling intervention is not an effective way to reduce student loneliness during the pandemic. A randomized controlled study is recommended for further exploration of the efficacy of e-journaling intervention.